2022
DOI: 10.1155/2022/8565490
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Electrical Impedance Tomography for Breast Cancer Detection: A Systematic Review and Meta-Analysis

Abstract: Introduction. Incidence of breast cancer (BC) in 2020 is about 2.26 million new cases. It is the first common cancer accounting for 11.7% of all cancer worldwide. Disease complications and the mortality rate of breast cancer are highly dependent on the early diagnosis. Therefore, novel human breast-imaging techniques play an important role in minimizing the breast cancer morbidity and mortality rate. Electrical impedance tomography (EIT) is a noninvasive technique to image the breast using the electrical imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Breast cancer (BC) is a frequent disease in females [ 1 ], with a certain genetic risk [ 2 ]. According to the latest global cancer statistics, the number of new BC cases reaches 2.26 million, making it the world's biggest cancer, accounting for 11.7% of all new cancer patients, and its mortality rate is about 6.6% [ 3 ]. In the early stages, 80% of patients often have breast lumps, nipple discharge, abnormal nipples, and areolas.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer (BC) is a frequent disease in females [ 1 ], with a certain genetic risk [ 2 ]. According to the latest global cancer statistics, the number of new BC cases reaches 2.26 million, making it the world's biggest cancer, accounting for 11.7% of all new cancer patients, and its mortality rate is about 6.6% [ 3 ]. In the early stages, 80% of patients often have breast lumps, nipple discharge, abnormal nipples, and areolas.…”
Section: Introductionmentioning
confidence: 99%
“…However, with sufficiently sensitive receivers, the detection of small tumors should be possible even in the most challenging cases. Due to this feature, microwave technique is considered to outperform other new techniques considered for portable early breast tumor detection applications, such as electro impedance tomography (EIT) and near infrared spectroscopy (NIRS) since EIT has limitations with spatial resolution and NIRS with penetration depth [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…EIT biological applications involved multiple tissue and organ such as the brain [ 23 ], breast [ 24 ], prostate [ 25 ], bladder [ 26 ], stomach [ 27 ], and blood vessels [ 28 ], etc., consistent with our result that keywords were clustered into 18 topics. The cluster intensity and the specific topic analysis showed that applications in brain anatomical structure, breast cancer, and hemodynamics were hot topics over time.…”
Section: Discussionmentioning
confidence: 99%